PENENTUAN FISHING GROUND DAN ALAT TANGKAP UNGGULAN IKAN PELAGIS DI KOTA BENGKULU - Zerli Selvika; Mustaruddin Mustaruddin; Roza Yusfiandayani (Jurnal Teknologi Perikanan dan Kelautan, 2018)
The fisherman of Bengkulu city to hunt the fishing ground for pelagic was still conventionally. Pelagic fish was catched by many types of fishing gear. For optimalizing sustainable pelagic fisheries was required the information about fishing ground distribution and selecting superior fishing gear for pelagic fish. The purpose of this study was to find out the fishing ground distribution and selecting superior fishing gear for pelagic fish. The method was used to find out the fishing ground distribution by mapping and selecting superior fishing ground by scoring the result showed that the fishing ground of pelagic was around Tikus island, Mega island, and Enggano island. Based on the standardization result of technic, biology, social, and economic aspect showed that selected fishing gear as superior fishing gears for pelagic were purse seine, boat lift net, and troll line. The selected fishing gear for pelagic fish was superior fishing gear of all alternative fishing gear for pelagic fish.